MEMAHAMI MEDIA PEMBELAJARAN SEBAGAI REFLEKSI KEMANUSIAAN DALAM PRAKTIK PENDIDIKAN - Hisbiyatul Hasanah (Al'Adalah, 2017)
Learning media in the world of education, the same discussion about humanity itself. Not only because education is a process of forming intellectual and emotional basic skills, but also in education there is a reflection of the human perspective on the relationship between humans and creators, humans with nature, and between humans. Actually, learning is a discussion of interaction and socialization that composes the self-concepts needed from the ability to interpret and support each other's actions. Through education, thus, one increasingly understands its nature as a social human who needs other people, the environment, and even meets God on the journey.